2010
DOI: 10.5511/plantbiotechnology.27.333
|View full text |Cite
|
Sign up to set email alerts
|

Gene dosage and genetic background affect miraculin accumulation in transgenic tomato fruits

Abstract: Gene dosage and genetic background are factors that influence transgene expression in transgenic plants. In our previous studies, we produced transgenic tomato plants that accumulate miraculin, a taste-modifying protein, in a genetically stable manner. To elucidate the effects of gene dosage and genetic background on miraculin accumulation in transgenic tomato fruits, we generated hybrid tomato lines between the homozygous transgenic line 56B (background cultivar 'Moneymaker') and the pure cultivars 'Micro-Tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
(30 reference statements)
1
11
0
1
Order By: Relevance
“…Ponnala et al [ 77 ] also showed a positive correlation between transcript levels and corresponding proteins in maize, in their case using non-GM varieties. In other GM crops, others have reported a correlation between transgene transcription and Cry1Ab concentrations for transgenic tomato [ 48 , 78 ] and cotton [ 29 , 30 ]. We are led to state, as a working hypothesis, that the crossing of the cry1Ab transgene into heterogeneous genetic contexts differs significantly from crossings within well-defined homogenous backgrounds.…”
Section: Resultsmentioning
confidence: 99%
“…Ponnala et al [ 77 ] also showed a positive correlation between transcript levels and corresponding proteins in maize, in their case using non-GM varieties. In other GM crops, others have reported a correlation between transgene transcription and Cry1Ab concentrations for transgenic tomato [ 48 , 78 ] and cotton [ 29 , 30 ]. We are led to state, as a working hypothesis, that the crossing of the cry1Ab transgene into heterogeneous genetic contexts differs significantly from crossings within well-defined homogenous backgrounds.…”
Section: Resultsmentioning
confidence: 99%
“…In order to overcome degradation of heterologous proteins, previous studies presented some potential solutions, such as to transport heterologous proteins to organelles. For example, the taste-modifying protein, miraculin was able to be accumulated in tomato fruit apoplast at levels over 150 µg/g fresh weight (Hiwasa-Tanase et al 2011;Kim et al 2010). Also, in the case of chloroplast, cry2Aa2 accumulated in tobacco leaf chloroplasts at a level over 70% of TSP (Oey et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…This could be the reason why some plants co-overexpressing multiple anti-stress genes don’t perform better than a single gene transgenic plants 22 , 23 . Besides, in some cases, variation of gene expression might even lead to totally unexpected plant phenotypes 24 .…”
Section: Introductionmentioning
confidence: 99%